1998
DOI: 10.1523/jneurosci.18-21-08814.1998
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Signal-Regulated Kinase (ERK) Controls Immediate Early Gene Induction on Corticostriatal Stimulation

Abstract: Activity-dependent changes in neuronal structure and synaptic remodeling depend critically on gene regulation. In an attempt to understand how glutamate receptor stimulation at the membrane leads to gene regulation in the nucleus, we traced intracellular signaling pathways targeting DNA regulatory elements of immediate early genes (IEGs). For this purpose we used an in vivo electrical stimulation of the glutamatergic corticostriatal pathway. We show that a transient activation of extracellular signal-regulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
248
1
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 306 publications
(276 citation statements)
references
References 74 publications
24
248
1
2
Order By: Relevance
“…The rats were killed 30 (for P-c-Jun and P-ERK1/2) or 90 min (for c-Fos) after the start of the final session or 30 or 90 min after the handling episode in the case of the naive animals. Alcohol relapse activates amygdala K Radwanska et al and c-Jun phosphorylation, respectively (Sgambato et al, 1998). Given the above, we decided to assess the activation pattern of phosphorylated, ie activated, ERK1/2 and JNK1/2.…”
Section: Behavioral Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…The rats were killed 30 (for P-c-Jun and P-ERK1/2) or 90 min (for c-Fos) after the start of the final session or 30 or 90 min after the handling episode in the case of the naive animals. Alcohol relapse activates amygdala K Radwanska et al and c-Jun phosphorylation, respectively (Sgambato et al, 1998). Given the above, we decided to assess the activation pattern of phosphorylated, ie activated, ERK1/2 and JNK1/2.…”
Section: Behavioral Parametersmentioning
confidence: 99%
“…It has been shown that c-Fos expression is induced in the amygdala after reexposure to drug-related stimuli (Brown et al, 1992;Neisewander et al, 2000;Ciccocioppo et al, 2001). The upstream regulators of this event are mostly unknown although possible candidates are extracellular signal-regulated kinases (ERK) which have been found to control c-fos expression in many experimental paradigms (Sgambato et al, 1998;Radwanska et al, 2005). Furthermore, ERKs have been shown to be activated in the central amygdala (CeA) after cue-induced relapse to cocaine seeking and inhibition of ERKs in the CeA decreased cocaine seeking after drug withdrawal (Lu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6). Furthermore, the transcription of Cu/ZnSOD is regulated by the transcription factor ELK-1 [35] and the promoter for MnSOD expression contain binding sites for Sp1, AP-1, and CREB [47,181], all of which have been linked to regulation by ERK1/2 [18,182] (Fig. 6).…”
Section: Nitric Oxide and Mapk Signalingmentioning
confidence: 99%
“…The expression of some enzymes implicated in antioxidant defences such as the enzymes for glutathione synthesis [235] and heme oxygenase [37] exhibit ERK1/2 dependency in the regulation of their expression. Furthermore, the transcription of Cu/ZnSOD is regulated by the transcription factor ELK-1 [35] and the promoter for MnSOD expression contain binding sites for Sp1, AP-1, and CREB [35,47], all of which have been linked to regulation by ERK1/2 [34,182].…”
Section: Flavonoids: Neuroprotective Agents In Vivo and In Vitro?mentioning
confidence: 99%